Implementasi Talent Management Untuk Pemulihan UMKM - Agustin Amborowati; Yeni Fajariyanti; Haryanto Haryanto; Agreianti Puspitasari (Publikasi Indonesia, 2022)
The outbreak of the covid-19 virus has had a broad impact on the Soloraya economy. Not only slowing down, not even a few have to stop operating. The implementation of the National Economic Recovery (PEN) program launched by the government to help cooperatives and MSMEs affected by the Covid-19 pandemic continues. The absorption of PEN funds has reached IDR 87.083 trillion or 70.37% of the total budget allocation of IDR 123.46 trillion. The realization of Productive Presidential Assistance for Micro Enterprises (Banpres Produktif) has reached 100% realization with a budget value of Rp28.8 trillion. The realization of this assistance has moved 12 million micro business actors who have experienced difficulties due to Covid-19. Based on PEN budget absorption data, the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia (KEMENKOP) is optimistic that the contribution of MSME exports will increase during the Covid-19 pandemic. If in 2020 MSME exports were around 14.37% of total exports, in 2021 it is targeted to increase to 15.12%. KEMNKOP's optimism about the increase in export contribution must also be balanced with the ability of MSME human resources. There are 8 things that need to be considered in handling Talent Management in Indonesia, namely organizational strategy and talent definition, talent identification, training and empowerment, appreciation, involvement, retention and career path, total quality management, and technology. The integrated talent management system model consists of corporate strategy, business strategy, attracting, developing, retaining, and evaluation of effectiveness. Where all these activities are directly supported by talent mindset culture, management support, and adequate Human Resourcer Information System. The research flow begins with an exploratory process in determining independent variables and designing research instruments. This stage includes Focus Group Discussion (FGD), Indepth Interview. Furthermore, face validity and small-scale and large-scale instrument testing. In this study, researchers will describe the implementation of Talent Management in MSMEs in Surakarta City. The sample criteria are employees at MSMEs registered with the Office of Cooperatives and SMEs of the Surakarta City Government. In this study, literature data comes from books, journals, the internet, research results and other information deemed relevant to the research topic.